tDCS cranial nerve Co-stimulation: Unveiling brainstem pathways involved in trigeminal nerve direct current stimulation in rats - Alireza Majdi; Liyi Chen; Lars E. Larsen; Robrecht Raedt; Myles Mc Laughlin (Brain Stimulation)
Background: The effects of transcranial direct current stimulation (tDCS) are generally thought to result from the polarization of cortical neurons by the weak electric fields it creates. However, recent evidence suggests that some tDCS effects may be mediated through co-stimulation of peripheral or cranial nerves, particularly the trigeminal nerve (TN). The TN projects to key brainstem nuclei that regulate neurotransmitter release throughout the central nervous system, but the specific pathways involved are not yet well understood. Methods: In this study, we examined the effects of acute transcutaneous TN direct current stimulation (TN-DCS) on tonic (i.e. mean spike rate) and phasic (number of bursts, spike rate per burst, burst duration, and inter-burst interval) activities while simultaneously recording single-neuron activity across three brainstem nuclei in rats: the locus coeruleus (LC; phasic and tonic activities), dorsal raphe nucleus (DRN; tonic activity), and median raphe nucleus (MnRN; tonic activity). Results: TN-DCS significantly modulated tonic activity in the LC and DRN, with interactions between amplitude, polarity, and time affecting mean spike rates. It also influenced phasic activity in the LC, altering burst number, duration, and inter-burst intervals. In contrast, MnRN tonic activity was unchanged. Blocking TN with xylocaine eliminated the effects on tonic activity in both the LC and DRN. Conclusions: These results suggest that tDCS may modulate the TN, altering DRN and LC activity. Differential changes in tonic and phasic LC activity highlight their roles in TN-DCS effects on the cortex. This research offers insights to improve tDCS efficacy and understanding. Keywords: tDCS; trigeminal nerve; locus coeruleus; Dorsal raphe nucleus; median raphe nucleus.